MERCOSUR: INTEGRATION COMPROMISE OF THE SOUTH - D. V. Koshkul (Финансы: теория и практика)
The article contains preliminary results of a research dedicated to the integration process taking part within the Mercosur subregional bloc in Latin America.Based on detailed examination of the Mercosur legislative framework as well as of working papers prepared by its bodies the research included analysis of key aspects of the Mercosur integration model, particularly of the main integration principles and their development.Topicality of the article is predetermined primarily by the potential which integration process has for promotion of international economic and financial stability under globalization.In author’s opinion regional integration helps provide a reasonable compromise between the task of self-sufficient economic development in emerging countries and the one of improving their participation in the world economywhile reducing exposure to financial risks and turbulences.Mercosur integration principles contain a special approach to realization of the compromise above which is based on development of productive integration between countries, their structural transformation and deepening of intraregional monetary and financial cooperation.It’s worth underlining that the problems set in the article are of special relevance for Russia as it is involved into the process of eurasian integration and is currently in a state of high external financial vulnerability caused by the sanction policies and the fall of oil prices. The experience of Latin America may broaden approach to these challenges.